Miscible blends of biobased poly(lactide) with poly(methyl methacrylate): Effects of chopped glass fiber incorporation. Issue 22 (22nd February 2017) - Cousins, Dylan S.; Lowe, Corinne; Swan, Dana; Barsotti, Robert; Zhang, Mingfu; Gleich, Klaus; Berry, Derek; Snowberg, David; Dorgan, John R.
ABSTRACT: Poly(lactide) (PLA) and poly(methyl methacrylate) (PMMA) are melt compounded with chopped glass fiber using laboratory scale twin‐screw extrusion. Physical properties are examined using differential scanning calorimetry (DSC), dynamic mechanical thermal analysis (DMTA), thermogravimetric analysis (TGA), tensile testing, impact testing, X‐ray computed tomography (CT) scanning, and field emission scanning electron microscopy (FE‐SEM). Molecular weight is determined using gel permeation chromatography (GPC). Miscibility of the blends is implied by the presence of a single glass transition temperature and homogeneous morphology. PLA/PMMA blends tend to show positive deviations from a simple linear mixing rule in their mechanical properties (e.g., tensile toughness, modulus, and stress at break). The addition of 40 wt % glass fiber to the system dramatically increases physical properties. Across all blend compositions, the tensile modulus increases from roughly 3 GPa to roughly 10 GPa. Estimated heat distortion temperatures (HDTs) are also greatly enhanced; the pure PLA sample HDT increases from 75 °C to 135 °C. Fiber filled polymer blends represent a sustainable class of earth abundant materials which should prove useful across a range of applications. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44868. Abstract :